Future food systems: challenges and consequences of the current food system - Tutundjian, S.; Clarke, M.; Egal, F.; Dixson-Decleve, S.; Candotti, S. W.; Schmitter, Petra S.; Lovins, L. H. (Springer, 2021)
Humanity is in a planetary emergency. Agriculture and food systems are contributing to an interconnected global environmental crisis, with increasing risks, social instability, and conflict. This chapter examines the challenges, drivers, and consequences of unsustainable agriculture and food systems, recognizing these are diverse and multi-scale. It presents a vision for sustainable, nutritious, and equitable food systems. Currently, food systems are a significant driver of climate change, nature loss, and pollution, as well as poor health and poverty, with inequitable access to resources and benefits from food systems. Fundamentally, the systems change needed is to transform terrestrial and aquatic food systems so that they become part of the solution for sustainability, not part of the problem. A safe future for humanity requires radical transformations ranging from agricultural production systems through dietary patterns and waste disposal. The focus is on the broad categories of innovation and sustainable technologies considered to have critical potential in pathways that enable transition to a more resilient and equitable system. Governance is a key enabling condition and needs to be based on food as a human right, not simply as a commodity. Multilevel governance underpins the development and implementation of territorial food systems strategies, which can provide effective integration of multiple solutions. Humanity is at an existential turning point and has a narrow window to act now to reduce risk and avoid catastrophe. The rules governing our food systems are human made – and it is within the gift of humanity to change them.